An increase of NAD+ kinase activity in Neurospora cells during adaptation to environmental stress - T. P. Afanasieva; S. Yu. Filippovich; M. S. Kritsky (Fungal Genetics Reports, 1984)
An increase of NAD+ kinase activity in Neurospora cells during adaptation to environmental stress